Carbon from carbon dioxide via molten carbonate electrolysis: fundamental investigations - Lawrence, Richard Charles (2013)
Conversion of carbon dioxide into useful products has become highly desirable in recent years in order to both mitigate carbon dioxide emissions to the atmosphere and develop non-fossil energy sources. A variety of methods exist for the electro-reduction of carbon dioxide in solution to useful products, such as carbon monoxide and hydrocarbons. However, none of these processes are able to directly convert carbon dioxide to carbon.